Biochemical characterization of alien H-2 antigens expressed on a methylcholanthrene-induced tumor. - Rogers, M J (1979)
A methylcholanthrene-induced tumor of BALB/c (H-2d) origin had been shown to express H-2 antigens normally associated with the H-2k haplotype. The molecules expressing the alien antigens have been partially purified and shown to be distinct from molecules expressing normal H-2d antigens. Like normal H-2 antigens, the alien antigens have a molecular weight of 48,000, are glycoproteins, and are noncovalently bound to beta 2-microglobulin. The alien antigens differ from normal H-2 antigens in their susceptibility to papain digestion, behavior during gel filtration, and overall stability. Possible mechanisms accounting for the expression of the alien antigen are discussed.